Pengaruh Literasi Keuangan, Gaya Hidup, dan Electronic Money terhadap Perilaku Konsumtif (Studi Kasus Pada Mahasiswa Manajemen Universitas Islam Malang Angkatan Tahun 2020-2022) - Zahro, Handini Nur Chameli Atuz; Mardani, Ronny Malavia; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The objective of this study is to examine and elucidate how consumer behavior is impacted by financial literacy, lifestyle, and electronic money. Case Study of Management Students at the Islamic University of Malang Class of 2020-2022. A sample of one hundred respondents was selected using random sampling methods from the Slovin formula for this study. This study used multiple linear regression analysis as a quantitative data analysis tool. Partial hypothesis testing is done using the data. The study's findings indicate that, to a lesser extent, the Lifestyle variable and the Financial Literacy variable have a significant impact on the purchase behavior of students enrolled in the Management study program at the Islamic University of Malang. Malang, the Lifestyle variable has a significant influence on the Consumptive Behavior of Management study program students at the Islamic University of Malang, Islamic University of Malang, and Electronic Money has a significant influence on the Consumptive Behavior of Management study program students at the Islamic University of Malang, Malang. Keywords: Financial Literacy, Lifestyle, Electronic Money, Consumptive Behavior